CLUSTER CREATING CONDITIONS - Yu. N. Lapygin; D. V. Tulinova (Вестник университета)
The dynamics of cluster formation in the context of the federal districts and Russia as a whole has been considered, trends in the development of cluster initiatives, as well as the basic principles for creating clusters have been analysed. It is shown that, since 2015, there has been a significant decrease in growth, and the Central Federal and Volga Federal districts are leading among the Federal subjects. It has been identified that in the process of creating a cluster the conducting approach dominates, which is manifested in the initiative of the state. It has been noted that among the principles of cluster formation, traditional rules prevail that are typical for world practice. An algorithmic scheme for creating a cluster based on the results of the formation of a cluster strategy with the subsequent development and implementation of a project to create such a cluster has been constructed.